Efficiency of Training: A Comparative Study on some Selected Commercial Banks in Bangladesh - Islam, Md. Zahidul (Journal of Asian Business Strategy, 2015)
Most of the commercial banks in Bangladesh arrange different training programs for adapting their existing human resources to their jobs and also updating new information or techniques and reshaping their knowledge. The purpose of the paper is to discover the level of efficiency of training among different commercial banks in Bangladesh. The study is mostly plunked on primary data that were composed from 100 employees as sample of different banks in Dhaka. Some statistical tools like mean standard deviation, hypothesis etc. were used for analyzing data in this paper. The study reveals that most of the commercial banks arrange initial training and in house training but they do not arrange mid level or advanced training as well as off the job training. Most of the banks in Bangladesh do not frequently arrange training programs. The average level of efficiency of training of all banks is 77.08%. The levels of efficiency of training from higher to lower level are as follows: DBBL, BBL, IBBL, TBL and ABL.